Dampak Kerusakan Dini Perkerasan Jalan terhadap Kerugian Aspek Finansial - Simamora, Marsinta; Trisnoyuwono, Diarto; Muda, Anastasia Hendrina (MEDIA KOMUNIKASI TEKNIK SIPIL, 2018)
National road management is not optimal and inefficient, the indications can be seen from the number of early damage cases of the road construction found. Indeed, natural damage to road construction is unavoidable but it becomes a problem if the damage occurs not long after the road product is handed over to the road manager or the government. Then the next question can arise whether the phenomenon of early pavement damage will cause harm to both road users and the government.This study aims to show the thinking framework of financial consequences and apply it through a model due to the occurrence of premature damage. Referring to the concept of benefit value that is represented by road conditions over the life of the service, then roads that have been damaged before their construction ends will result in losses due to loss of benefits. Based on this concept, a simulation was conducted using a national road data. Simulation results show that there is an estimated financial loss due to the occurrence of early damage. For early damage with a condition value of loss of 36 then the estimated loss is Rp 458,257,899.41 per kilometer. Estimated average loss per kilometer for each loss of one unit of condition value is Rp 12,72,386.09. The results of this study also show that roads that do not suffer early damage do not cause losses or losses are zero.